 # The value of $\left( -24 \right)+\left( -28 \right)=$A. -52B. +52C. 0D. None
In the question, we have been asked to find the value of $\left( -24 \right)+\left( -28 \right)$. Before proceeding with the question, we must know about the BODMAS rule. BODMAS is an acronym which stands for Bracket, Of, Division, Multiplication, Addition and Subtraction. It explains the order of the operations required to solve an expression. According to the BODMAS rule, if an expression contains brackets ((), {}, []), we have to first solve or simplify the bracket followed by of (powers and roots etc.), then division, multiplication, addition and subtraction from left to right. Solving the problem in the wrong order will result in a wrong answer.
Let us consider the expression given in the question, $E=\left( -24 \right)+\left( -28 \right)$. We know that according to the BODMAS rule, we must solve the bracket of the expression first. According to arithmetic rules, we know that $+\left( -a \right)=-a$. By using this in the above expression, we get, $E=\left( -24 \right)-28$. We also know that $\left( -a \right)=-a$. So, by using this in the expression, we get, $E=-24-28$. We know that $-a-b=-\left( a+b \right)$. So, using this in the expression, we get, $E=-\left( 24+28 \right)$. By simplifying the expression further, we get, $E=-\left( 52 \right)\Rightarrow E=-52$.
Hence the value of $\left( -24 \right)+\left( -28 \right)=-52$. Therefore, the correct answer is option A.
Note: The students must remember the BODMAS rule here along with the basic arithmetic rules like, $\left( -\left( -a \right) \right)=a,\left( +\left( +a \right) \right)=a,-\left( +a \right)=-a,+\left( -a \right)=-a$. These rules are very important in almost every area of mathematics, so there should be no confusion while solving questions that involve such operations. Always remember to solve the problem according to the BODMAS rule, solving it in the wrong order would lead to a wrong answer.